Banks' strategic interaction, adverse price dynamics and systemic liquidity risk - Ulrich Krüger; Christoph Roling; Leonid Silbermann; Lui Hsian Wong (Deutsche Bundesbank, 2022)
In this paper we introduce two measures, the Systemic Liquidity Buffer (SLB) and the Systemic Liquidity Shortfall (SLS) to assess liquidity in the banking system. The SLB takes an aggregated perspective on liquidity risks in the banking system. In contrast, the SLS focusses on the problematic banks which suffer a liquidity shortfall. These measures provide an add-on to regulatory liquidity measures such as the LCR because they better incorporate a systemic perspective: (1) They model the impact of a funding shock by valuing assets at depressed market prices, (2) Doing so, they explicitly incorporate banks' strategic responses to a market undergoing sharp price declines. We test our approach using several applications capturing both a short (5 days) and a medium-term (30 days) stress scenario, a sudden rise in interest rates, the impact of banks' US dollar business and the recent COVID-19 crisis.
Keywords: C63; G01; G17; G21; G28; 330; Systemic liquidity risk; market liquidity; funding liquidity; contagion; fire sales